Pengelolaan Program Kursus Dan Pelatihan Dalam Meningkatkan Kewirausahaan Peserta Didik Di SKB Purwokerto - Indah Parasmita; Heru Kurniawan; Amalia Nurbaiti; Musyafa Ali (Jurnal Pendidikan Nonformal, 2022)
SKB Purwokerto is a nonformal educational institution organizing Courses and Skills Program activities which one of its important objectives is to instill entrepreneurial spirit in students. This form of entrepreneurial spirit planting is done in the form of management or management of courses and skills. Its management is carried out through five important activities: (1) planning activities in determining the objectives, one of which is the planting of entrepreneurial spirit in learners through course activities and training conducted; (2) entrepreneurial organizing activities shall be conducted in the form of incorporating aspects of entrepreneurship in materials and modules, delivery of entrepreneurial materials by presenters and resource persons, and knowledge and skills of entrepreneurship by learners; (3) implementation activities in the implementation of entrepreneurial spirit shall be carried out in direct practice activities of learners during activities and in public life; (4) coordination activities shall be carried out in the form of communicating the entrepreneurial spirit with the learners so as to make the learners have a strong motivation to develop the business on the abilities and skills obtained; and (5) entrepreneurial supervision activities conducted in the form of instilling entrepreneurial spirit in assessment, guidance, mentoring, and consulting activities oriented to continuously increase the entrepreneurial spirit of learners